The Theory of Max Weber as a Methodology of Sociological Analysis for Understanding the Foreign Policy of Modern China - N. B. Pomozova (Дискурс, 2022)
Introduction. The multi-vector strengthening of China leads to a lively international expert discussion. This article examines the possibilities of applying the methodology developed by M. Weber to the analysis of modern Chinese foreign policy. Despite the fact that M. Weber's studies were published more than a hundred years ago, his approaches, when correlated with modern realities, do not lose their relevance today.Methodology and sources. The research is based on the methodology proposed by M. Weber and its potential for analysis of the modern foreign policy of the PRC.Results and discussion. The influence of Confucianism on China’s foreign policy increased with the coming to power of Xi Jinping. So, China demonstrates a desire for a legalcharismatic type of domination (according to M. Weber), subordinating its will to other actors of international relations, and as one of the tools to ensure legitimacy to its domination uses the socialist values formulated in 2012. The desire for rationalization (according to M. Weber) is reflected, among other things, in the priority of the technological development of the PRC, the development and implementation of artificial intelligence as its (rationality) pure form in the modern sense.Conclusion. Analysis of the potential of M. Weber's methodology in relation to sociological research peculiarities of the PRC's foreign policy strategy shows that in the implementation of international policy China is inherently gravitating towards legal-charismatic domination (according to M. Weber), endowed with a rational character and possessing three types of rationalization. At the same time core socialist values are one of the tools to ensure the legitimacy of domination.